Educational Program for Promoting Breast Self-Examination: A Literature Review - Juanita Juanita; Piyanuch Jittanoon (Idea Nursing Journal, 2018)
ABSTRACTBreast cancer was the most common type of cancer in women worldwide. It was the leading cause of death in young women. Therefore, detected breast cancer in the early stage were needed. Breast self-examination was one of methods can detect breast cancer. In addition, program that promote BSE was important to incerase awarness of women to perform BSE. The study aimed to to find or formulate the applicable, effective, and efficient educational program for promoting BSE. Methods of the study by using electronic databases, such as CINAHL, Pub Med, Science Direct, and Ovid. The articles which were included in this review were published from 1990 to 2010. The study also used the universal case entry website like goggle-web and goggle-scholars. The keywords that already used such as the effect of educational program for promoting BSE, breast cancer screening, breast self-examination, program for promoting BSE, breast cancer, factors influencing BSE, define of BSE, factor related to BSE practice. The results of the study were categorized into five main topic such as concept of BSE, factors related to BSE practice, educational program for promoting BSE, strengths and weakness of those program, and recommendation. Conclusion and recomendation, most of the program effectiveness to increase BSE practice and BSE self-efficacy among women, but many factors influence the program such as cultural, level of knowledge, and demographic data. Besides, most of the programs use the HBM and SCT to develop their program, because both of these theories have variables that can encourage women to perform BSE. But, both of the theories did not consider the important role of cultural on health behavior, which it can affect of the BSE practice and self-efficacy. In addition, for the further recommended program should consider the role of cultural and use multifaceted method to improve BSE practice. Keywords: Breast cancer, educational program, cultural sensitivity.